Understanding the receiving countries' perspectives on transnational education: A phenomenological study in Egypt - Ibrahim, Bola (AUC Knowledge Fountain, 2020)
Transnational education (TNE) is the stone thrown into the still waters of higher education in Egypt, it has been expanding in scale and significance in the past few years, and already brought itself to the fore. This qualitative research aspires to explore the views of higher education stakeholders in Egypt on the rationales, motives, and implications of hosting TNE. The study seeks to answer two research questions; 1) how do higher education stakeholders view the rationales, motives, and value of TNE provisions in Egypt as a host country, and 2) how are the economic, pedagogical, and socio-cultural implications of TNE perceived by stakeholders in Egypt. The study adopted a qualitative design combining two methods of inquiry (phenomenology and document analysis) to conduct the research at hand. The study included fieldwork of fifteen research interviews, covering a wide range of higher education stakeholders such as policymakers, senior government officials, higher education experts, university president, TNE and public university faculty, and students. The document analysis focused on the policy level analyzing the new legal provision of TNE in Egypt, as well as the higher education strategic priorities enacted in major government strategies in the 2030 vision. The theoretical framework encompasses the institutional theory, both the cultural cognitive and the rational choice versions, and the human capital theory as the lenses from which the results are interpreted and analyzed. The notion of globalization is also used as the meta-theory that can help provide a macro-level analysis and contextualization of TNE in host countries. The findings indicate that the position and impact of TNE in Egypt are not yet fully understood. The findings suggest that TNE is a highly circumstantial phenomenon that differs from a context to another. The views of higher education stakeholders fluctuate between enthusiasm and doubt. The direct higher education stakeholders (the optimists), who are involved in the TNE business, hope that TNE creates momentum in the local higher education system that improves access, encourages quality, and stimulates the better performance. Nevertheless, the indirect stakeholders (the skeptics), those who are involved in public higher education in Egypt, thought that transnational education is exclusive to the Egyptian elite and that there are pedagogical and cultural barriers to integrating it within the broader higher education sector.